2022
DOI: 10.1111/ajt.17053
|View full text |Cite
|
Sign up to set email alerts
|

The use of normothermic liver preservation in combined liver and lung transplantation: A single-center experience

Abstract: Combined liver and lung transplantation (CLLT) is indicated in patients with both end‐stage liver and lung disease. Ex‐situ normothermic machine perfusion (NMP) has been previously used for extended normothermic lung preservation in CLLT. We aim to describe our single‐center experience using ex‐situ NMP for extended normothermic liver preservation in CLLT. Four CLLTs were performed from 2019 to 2020 with the lung transplanted first for all patients. Median ex‐situ pump time for the liver was 413 min (IQR 400–4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…One patient developed intra-operative post-reperfusion syndrome, but none of the patients developed secondary liver IRI. 108 These reports show that MP is feasible in combined liver transplantation, but randomized controlled trials are needed to substantiate its beneficial aspects in MOT.…”
Section: Innovative Techniques: Organ Preservation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One patient developed intra-operative post-reperfusion syndrome, but none of the patients developed secondary liver IRI. 108 These reports show that MP is feasible in combined liver transplantation, but randomized controlled trials are needed to substantiate its beneficial aspects in MOT.…”
Section: Innovative Techniques: Organ Preservation Methodsmentioning
confidence: 99%
“…107 The Henry Ford Hospital in Detroit, Michigan reported that they used NMP successfully in four patients undergoing CLLT. 108 The lung portion was transplanted first, and the median duration of liver NMP was 413 minutes. One patient developed intra-operative post-reperfusion syndrome, but none of the patients developed secondary liver IRI.…”
Section: Innovative Techniques: Organ Preservation Methodsmentioning
confidence: 99%
“…Patients suffering from >1 end-stage organ disease 97 (eg, heart-lungs, 98 liver-lungs, 97,99 or liver-kidney 100 ) can undergo multiorgan transplantation. Clinical case reports have evaluated NMP's applicability during combined liverlung transplantation in prolonging preservation times of 1 implicated organ (ie, liver 77 and lungs [101][102][103] ). Interestingly, Leeuwen et al used lung NMP and liver HMP in the first published case of combined liver and lung ex vivo machine perfusion for subsequent combined liver-lung transplantation.…”
Section: Multiorgan Transplantationmentioning
confidence: 99%
“…The maximum time under NMP depends on the system employed; for instance, the Liver Assist device (XVIVO Perfusion AB, Göteborg, Sweden) is recommended for up to 6 h (prolonged to 9 h in some studies 35,42 with total perfusion times usually extended by adding COR or HMP 17,18,39,42,45 ). Likewise, the Organ Care System device (OCS, Transmedics Inc., Andover, USA) for the liver can be safely used for up to 8 h 77 ; this device prompted a reduction in allograft dysfunction, ischemic biliary complications, and IRI compared with SCS and an increase in the number of transplantable donated-after-circulatory-death (DCD) livers. 43…”
Section: Nmp Devices In Clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation